Pembentukan Karakter Religius Siswa Melalui Kegiatan Dewan Jama'ah Mushola (DJM) Di SMK PGRI 2 Kota Kediri - Sulistiyorini, Defi; Nurfalah, Yasin (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
This study aims to determine the formation of the religious character of students through the activities of the Jamaah Mushola Council (DJM) at SMK PGRI 2 Kota Kediri. This study departs from three questions, "How is the formation of the religious character of students on the Aqidah dimension through the activities of the Jamaah Mushola Council (SMK) at SMK PGRI 2 in Kediri City? PGRI 2 City of Kediri ?, How is the formation of the religious character of students in the Moral dimension through the activities of the Council of Jamaah Mushola (DJM) at SMK PGRI 2 Kota Kediri? ". With these three questions, the results of the study found that: (1) The formation of religious character in the Aqeedah dimension through Islamic study activities whose material discusses Islamic law, and the recitation of the book Mabadi 'Al-fiqhiyyah. (2) The activity of forming religious characters in the dimension of worship is through the activities of the habituation of the dhuhur prayer in congregation, diba'iyyah, the art of reading the Koran, and the khotmil of the Quran. (3) The formation of religious character in the moral dimension, namely by using the habitual method with good character, which is done by familiarizing students to be polite to anyone and wherever they are.